2015
DOI: 10.1007/s12307-015-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of M1/M2 Tumour-Associated Macrophages (TAMs) and Th1/Th2 Cytokine Profiles in Patients with NSCLC

Abstract: Lung cancer is one of the most commonly reported cancers, and is known to be associated with a poor prognosis. The function of tumour-associated macrophages (TAMs) in lung cancer patients is multifaceted and the literature shows conflicting roles. (I) To analyze the Th1 and Th2 cytokine levels that contribute to the differentiation of M1 and M2 macrophage populations in the serum of patients with NSCLC versus non-cancer controls; and (II) To characterize the M1 and M2 macrophage populations within TAMs in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 48 publications
2
109
0
1
Order By: Relevance
“…Thus, many plasma proteins were detected in BALF, indicating that BALF is a great source of biomarkers for lung cancer. Indeed, these findings are in line with that of other studies published elsewhere (e.g., ANXA2) …”
supporting
confidence: 93%
See 1 more Smart Citation
“…Thus, many plasma proteins were detected in BALF, indicating that BALF is a great source of biomarkers for lung cancer. Indeed, these findings are in line with that of other studies published elsewhere (e.g., ANXA2) …”
supporting
confidence: 93%
“…This is probably because we combined the depletion with high pH RPLC fractionation. As shown in Figure , the numbers of identified BALF proteins in other studies were smaller than that of our study, ranging ≈800 to 1500 proteins . Next we compared our result with lung tumor proteome and human plasma proteome datasets .…”
mentioning
confidence: 59%
“…The higher percentage of M2 TAMs in LUAD than LUSC tissues suggests that TAMs may tend to differentiate into the M2 subtype in the LUAD microenvironment, while most TAMs differentiate into the M1 subtype in LUSC. This differentiation may be responsible for the opposing roles of CCL2 or CCL4 for predicting prognosis in patients with LUAD and LUSC …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies showed that M1 cytokines (e.g., IFN-γ, TNF-α, IL-1β, IL-2, and IL-12) and their receptors were virtually absent in glioma, brain metastatic cell lines, and in human tissues whereas M2 immunosuppressive cytokine (i.e. IL-6, TGF-β) were greatly predominant in these cells (77, 8587). Therefore, in brain tumor, the balance of upregulating M2 pro-tumor response and attenuated M1 anti-tumor immune response determine the promotion of tumor growth and invasion.…”
Section: Cross-talk Between Microglia/macrophages and Tumor Cells mentioning
confidence: 99%